2015
DOI: 10.1002/anie.201507418
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Studies of the Karlotoxin Class Using NMR Spectroscopy and DP4 Chemical‐Shift Analysis: Insights into their Mechanism of Action

Abstract: Following the publication of karlotoxin 2 (KmTx2, 1), the harmful algal bloom dinoflagellate Karlodinium sp. was collected from oceans and bays throughout the world and scrutinized to identify additional biologically active complex polyketides. The structure of 1 was validated and revised at C49 using computational NMR tools including J-based configurational analysis (JBCA) and chemical shift (CS) calculations. The characterization of 2 new compounds [KmTx8 and 9 (2–3)] was achieved through overlaid 2D HSQC NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 30 publications
1
48
0
Order By: Relevance
“…Multiple types of KTXs are known to occur (Place et al, 2012; Waters et al, 2015). All of them have the same basic structure but differ in the number of carbons in the main carbon backbone and the nature of certain functional groups in the molecule.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple types of KTXs are known to occur (Place et al, 2012; Waters et al, 2015). All of them have the same basic structure but differ in the number of carbons in the main carbon backbone and the nature of certain functional groups in the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The semi-purified fractions of KTXs were further enriched and characterized by LC–MS/MS and NMR as described by Waters et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…1). The computed chemical shifts of the (2″ R )- and (2″ S )-diastereomers of 6 were compared with the experimental values [45, 46] utilizing total absolute deviation (TAD) and DP4 probability analyses, both of which have been successfully applied in addressing stereochemical details of a wide array of compounds [30,36,4851]. While the TAD analysis favored the (2″ R )-diastereomer, but with only a slight difference relative to the other diastereomer (Table 2), DP4 analysis predicted the structure of 6 as the (2″ R )-diastereomer of 6 with 100% probability (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5). In a recent investigation on the mechanism of action, Waters et al (2015) showed that KmTx binds to a sterol on the cell membrane, and inserts the polyol arm into it, to form a pore on the cell membrane with multiple molecules in a micelle-like interaction. The saturated polyol arm may have better structural flexibility, which would promote the pore formation process.…”
Section: Discussionmentioning
confidence: 99%
“…The unique structure enables karlotoxins to form pores in cell membranes leading to cell lysis through colloid osmolysis (Deeds et al, 2006). During pore formation, karlotoxins selectively bind 4-desmethyl sterols in cell membranes (Adolf et al 2006a; Deeds and Place, 2006) making them important marine drug candidates for the treatment of severe human health issues including heart disease and cancer where cholesterol is involved (Waters et al, 2010; Waters et al 2015). …”
Section: Introductionmentioning
confidence: 99%